AN ANALYSIS OF THE IMPACT OF MULTIPLAYER ONLINE BATTLE ARENA (MOBA) GAMES TOWARD LISTENING COMPREHENSION - Godefridus Bali Geroda (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
The user of online games in this world has increased rapidly year by year. The last data has shown that there are 699 million active users around the world. Indonesia is become one of the most country who consumed the online game. This research aims to determine, how online games are played by the students, the causes of the students play the online games and the effect of the online game or MOBA game on the students’ listening comprehension as the main goal. This research used Mixed-method. The data is used questionnaire, listening test, interview, and documentation. 62 students have taken for the sample. Based on the research that has been done, the researcher can conclude that the online game gives the impact to the listening comprehension of the students at SMKN 6, Samarinda. It proved by the mean score pre-test and post-test in experimental group was 69.67 that increased into 84.03 after treatment. Therefore, the display data of sample T-test has shown that value sig. (2-talled) is 0.00 < 0.05 with the R square 0.76. It means there is significant influence of playing online game on the student’s listening skill of 76%.